Devonian and carboniferous palynostratigraphy of the South Portuguese zone, Portugal - an overview - Pereira, Zélia (2014)
The South Portuguese Zone (SPZ) represents the southern branch of the Iberian Variscides and comprehends the following geologic domains: the Pulo do Lobo Antiform, the Iberian Pyrite Belt, the Baixo Alentejo Flysch Group and the Southwest Portugal (Aljezur and Bordeira Anticlines). An overview of all the results recently achieved in palynostratigraphic research of selected sections all over the SPZ is presented. A chronostratigraphic correlation of the stratigraphic units recognized across the ZPZ and its geodynamic and palaeogeographic implications is attempted.